2021
DOI: 10.1021/acscatal.0c04104
|View full text |Cite
|
Sign up to set email alerts
|

A First-Principles Microkinetics for Homogeneous–Heterogeneous Reactions: Application to Oxidative Coupling of Methane Catalyzed by Magnesium Oxide

Abstract: The oxidative coupling of methane (OCM), a major catalytic reaction in natural gas utilization, was examined by first-principles density functional theory (DFT) calculations combined with microkinetic and reactor simulations. We investigated magnesium oxide (MgO), which is a standard catalyst for the OCM reaction. We used the stepped MgO as the catalyst model, as this surface is a strong candidate for the active site for the CH3 generation from CH4. Previous experimental and kinetic simulations have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that microkinetic analysis combined with first-principles calculations is able to represent surface reactions in heterogeneous catalysis. In general, a more detailed analysis of surface reactions is investigated using first-principles calculations. However, if a large amount of catalyst data is generated via first-principles calculations, it could be possible to uncover key knowledge and patterns for designing catalysts from a bird’s-eye point of view using catalyst informatics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that microkinetic analysis combined with first-principles calculations is able to represent surface reactions in heterogeneous catalysis. In general, a more detailed analysis of surface reactions is investigated using first-principles calculations. However, if a large amount of catalyst data is generated via first-principles calculations, it could be possible to uncover key knowledge and patterns for designing catalysts from a bird’s-eye point of view using catalyst informatics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is often more accurate than the kinetic analysis based on the global rate expression 11 . Currently, DFT-based microkinetics is widely used in catalysis research because it is a powerful tool that allows the calculation of kinetic information, such as the reaction energy and activation barrier, can be calculated by DFT 11 – 15 . Considering this, a combination of DFT calculations, microkinetics, and catalytic material generation from generative models could be a promising approach for the rational design of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, since surface species are difficult to observe or identify, OCM surface kinetics are indirectly investigated experimentally by extrapolating conversion rates and selectivity at zero methane conversion for initiation steps 8 , 12 , 37 39 or by applying isotopic techniques to identify the pathways of products. 8 , 17 , 40 42 Other than these, the parameters of surface elementary reactions (sticking coefficient and activation energy) are estimated mostly via density functional theory (DFT) calculations 43 54 or Polanyi relationships. 20 , 21 , 23 , 25 , 26 It is challenging to precisely predict the entire surface reaction mechanism for OCM, which indicates the critical role of an accurate and reliable gas-phase model over the entire mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Ishioka et al also used a machine learning technique to better understand the gas-phase performances against operating conditions from the high-throughput experimental data. In fact, since surface species are difficult to observe or identify, OCM surface kinetics are indirectly investigated experimentally by extrapolating conversion rates and selectivity at zero methane conversion for initiation steps ,, or by applying isotopic techniques to identify the pathways of products. ,, Other than these, the parameters of surface elementary reactions (sticking coefficient and activation energy) are estimated mostly via density functional theory (DFT) calculations or Polanyi relationships. ,,,, It is challenging to precisely predict the entire surface reaction mechanism for OCM, which indicates the critical role of an accurate and reliable gas-phase model over the entire mechanism. To fulfill this requirement, gas-phase reaction models should accurately describe well-known homogeneous processes (oxidation, pyrolysis, etc.…”
Section: Introductionmentioning
confidence: 99%